Breaking boundaries of hybrid photodetector: A novel approach for high-speed TCSPC with minimal distortion - P. Daniele; G. Fratta; I. Labanca; G. Acconcia; I. Rech (APL Photonics)
Time-Correlated Single-Photon Counting (TCSPC) enables the measurement of low-intensity optical signals with sub-picosecond timing resolution. Its performance has long been limited by pile-up distortion, which restricts acquisition rates to a small fraction (typically 5%) of the laser excitation rate. In this work, we break through these limitations in fluorescence measurements by harnessing the power of a hybrid photodetector and validating a novel, constraint-free methodology that removes pile-up distortion, enabling high precision in lifetime estimation. The mathematical framework underlying this method not only makes it possible to overcome the traditional distortion but also addresses previously unexplored error sources. For the first time, we present a real-time processing algorithm that compensates for hardware-induced distortions, achieving a comprehensive fluorescence histogram correction. Remarkably, with our approach, we achieve a count rate as high as 121% of the excitation rate, setting a new benchmark in TCSPC performance and representing a transformative leap forward in the capability of the technology to deliver high-speed and high-precision measurements.